Penggunaan Media Teknologi Informasi dalam Pembelajaran Pendidikan Agama Kristen di Masa Pandemi Covid-19 - Hermanto Sihotang (IMMANUEL: Jurnal Teologi dan Pendidikan Kristen, 2020)
Christian religious education has a strategic role in the inheritance of the values of Christian life and faith as taught by the Bible, the Word of God, which can take place in families, churches and schools. The complaint that is often heard from the school and teachers is the lack of interest in learning PAK by students, which can be caused by traditional learning strategies such as the use of one-way and monotonous lecture methods. In order to overcome this the teacher must implement a variety of learning strategies, including those that allow the use of information technology media in it. In addition, the covid-19 phenomenon is a new challenge, especially in the world of education - learning that cannot be done face-to-face. Therefore, teachers as educators in schools must optimize their insights and skills in information technology to be able to answer the challenges in question. Parents who are responsible for their children's education should create a good climate at home and facilitate children's learning facilities. Children as students are obliged to optimize gadgets as a source of learning, and develop skills in the field of information technology (computers, internet) as a means of learning during the Covid-19 pandemic. In this paper, descriptive qualitative methods or library research are used to obtain and analyze data regarding the use of information technology in the learning process of Christian religious education during the pandemic. The findings obtained are that the use of information technology in Christian religious education has basically become a demand for Christian religious education teachers, especially in the era of disruption. During the Covid-19 pandemic, these demands were far different, and made Christian religious education teachers even more motivated and inevitably had to adjust to online learning, master and apply this educational technology so that in the end it resulted in learning Christian religious education in schoolsAbstrakPendidikan agama Kristen memiliki peran yang strategis dalam pewarisan nilai-nilai hidup dan iman kristiani sebagaimana yang diajarkan Alkitab, Firman Allah, yang dapat berlangsung di keluarga, gereja dan sekolah. Keluhan yang sering terdengar dari pihak sekolah dan guru adalah kurangnya minat belajar PAK oleh peserta didik, yang hal ini bisa disebabkan oleh karena strategi pembelajaran yang tradisional seperti penggunaan metode ceramah yang bersifat satu arah dan monoton. Maka untuk mengatasi hal tersebut guru harus menerapkan strategi pembelajaran yang variatif termasuk yang memungkinkan penggunaan media teknologi informasi di dalamnya. Disamping itu, fenomena covid-19 menjadi tantangan baru, khususnya dalam dunia pendidikan - pembelajaran yang tidak bisa dilakukan dengan tatap muka. Oleh karena itu, guru sebagai pendidik di sekolah harus mengoptimalkan wawasan dan keterampilannya dalam hal teknologi informasi untuk dapat menjawab tantangan yang dimaksud. Orangtua sebagai penanggungjawab pendidikan anaknya hendaknya menciptakan iklim yang baik di rumah dan memfasilitasi sarana belajar anak. Anak sebagai peserta didik berkewajiban mengoptimalkan gadget sebagai sumber belajar, dan pengembangan keterampilan di bidang teknologi informasi (komputer, internet) sebagai sarana belajar pada masa pandemi covid-19. Dalam tulisan ini digunakan metode kualitatif deskriptif atau studi pustaka (library research) untuk memperoleh dan menganalisis data berkenaan dengan penggunaan teknologi informasi dalam proses pembelajaran pendidikan agama Kristen di masa pandemi. Hasil temuan yang diperoleh adalah bahwa pemanfaatan teknologi informasi dalam pendidikan agama Kristen pada dasarnya sudah menjadi tuntutan bagi guru-guru pendidikan agama Kristen, khususnya di era disrupsi. Di masa pandemi covid-19 tuntutan tersebut jauh berbeda, dan membuat guru-guru pendidikan agama Kristen semakin terpacu dan mau tidak mau harus menyesuaikan diri dengan pembelajaran daring, menguasai dan menerapkan teknologi pendidikan tersebut sehingga pada akhirnya memberhasilkan belajar pendidikan agama Kristen di sekolah.